Beyond the Assistant: Rethinking AI’s Role in Creative Media Workflows - Glover, Gordon (Proceedings of the International Conference on Networked Learning, 2026)
This round table explores a central question emerging across arts education: How can AI function as both an iterative creative tool and a proofreading, copyediting, and writing assistant—and what are the implications of integrating these tools into students’ creative workflows? As students increasingly incorporate AI into writing and media production, faculty face persistent challenges: uneven student ability in editing and revision, confusion about and resistance to the uses of AI, and concerns about diminishing authorship and originality. This discussion invites participants to examine AI’s dual promise and threat—its ability to scaffold students’ writing and iteration processes, its potential to undermine critical thinking, creative autonomy, and labor, and the problematic environmental, ethical, and cultural implications moving forward. Participants will engage with a project implemented in CRE125: Integrated Studio Foundations and CRE350: Creative Media Portfolio 2 (Fall 2025), where students use AI tools such as ChatGPT and Claude during brainstorming, drafting, editing, critique, and revision. These activities are framed with structured reflection and readings (e.g., Neil Postman’s Technopoly) to interrogate the cultural, ethical, and epistemological consequences of adopting new technologies. This round table aims to open an interdisciplinary conversation on the pedagogical, ethical, and creative stakes of AI integration in arts education—and to collaboratively define best practices for responsible, reflective use.